An exploratory study on the key success factors of transforming traditional manufacturing enterprises into sightseeing factories in southern Chinese Taiwan - Li Liou Yuan; Lu Kui Cheng; Wu Tai Ju; Chuang Ya Pei (Business Administration and Management Journal Review, 2020)
Economic globalization is not only an opportunity but also a challenge to enterprises. The challenges brought by economic globalization make enterprises face both survival war and economic competition. With the development of economic globalization, the enterprises in Chinese Taiwan are facing more and more competitive pressure. Therefore, it is a very important issue for enterprises how to comply with the trend of the times and solve the business difficulties. This paper makes a qualitative study on the successful enterprises in Chinese Taiwan by means of literature analysis, case study and in-depth interview. The researchers take the motivation and key success factors of Chinese Taiwan enterprises to transform into sightseeing factories as the research objectives and carry out exploratory research. The results show that the key success factors of the transformation from manufacturing enterprises to sightseeing factories can be the key success factors of three different forms of enterprise transformation: motivation dimension, technology dimension and activity dimension.